Just peachy - Ure, Jean (London : HarperCollins Children's Books, 2013)
I've always been the quiet one in my dramatic family. Not a drama queen, or a genius composer, or a twin, but Just Peachy. Mum says I've got my own thing going on ... I just wish I knew what that was! When I decide I want to attend Sacred Heart school rather than Summerville where my family have always gone everyone finally stops to listen! Stepping out on my own is scary, but I need space to find out who I am and what I'm good at.
Keywords: Identity (Psychology) -- Fiction; Psychological fiction